Hysteroscopic versus cervical injection for sentinel node detection in endometrial cancer: A multicenter prospective randomised controlled trial from the Multicenter Italian Trials in Ovarian cancer (MITO) study group. (November 2020) - Ditto, Antonino; Casarin, Jvan; Pinelli, Ciro; Perrone, Anna M.; Scollo, Paolo; Martinelli, Fabio; Bogani, Giorgio; Leone Roberti Maggiore, Umberto; Signorelli, Mauro; Chiappa, Valentina; Giorda, Giorgio; Scibilia, Giuseppe; et al.
Abstract: Aim: During the last years, the role of sentinel lymph node mapping (SLNM) for endometrial cancer (EC) surgical treatment has increased in popularity. However, several controversies remain about different technical steps of SLNM. Thus, a randomised control trial was designed to compare cervical (CI) and hysteroscopic (HI) indocyanine green (ICG) injection for SLNM of newly diagnosed EC undergoing surgical staging. The primary end-point of the study was to compare these two techniques in terms of para-aortic detection rate. Methods: Patients with apparent stage I or II histologically confirmed EC undergoing surgery were included in the study. This randomised trial distinguished patients in two study groups according to two different techniques of ICG SLNM: CI versus HI injection. Patients who met the inclusion criteria were randomly assigned to CI or HI injection in a 1:1 ratio. The central randomisation system allocated patient randomisation numbers sequentially in the order in which the patients were enrolled. This randomised trial was not blinded for either patients or the surgeons. Results: From March 2017 until April 2019, a total of 165 patients were randomised in this study: 85 (51.5%) in the CI group and 80 (48.5%) in the HI group. After randomisation, 14 (8.5%) patients were excluded from the study. Finally, 151 patients were included in the analysis: 82 (54.3%) in the CI group and 69 (45.7%) in the HI group. Hysteroscopy injection shows an ability to detect Sentinel nodes (SNLs) in the para-aortic area of about 10% greater compared with CI injection, although this difference did not reach statistical significance. The HI technique was superior in detecting isolated para-aortic SLNs (5.8% Versus 0%). The CI injection was correlated with higher SLN detection rates at the pelvic level compared with HI injection. Pelvic and overall detection was higher in the CI group. Conclusions: The present study supports the adoption of CI instead of HI injection because the former allows better identification of sentinel nodes (especially in the pelvic area). Detection of SLN in the para-aortic area was slightly higher in patients receiving a HI injection, but the difference with the CI route was not statistically significant. Highlights: Sentinel node mapping allows identification of extrauterine (i.e. lymphatic) disease. Cervical (CI) and hysteroscopic (HI) injections are to perform sentinel node mapping. CI and HI injections provide a similar detection rate in the para-aortic area. In comparison with HI injection, CI injection correlates with a higher pelvic sentinel node detection rate.